Protective Mechanisms of Carbon Monoxide and its Releasing Molecules against Ischemia-Reperfusion Injury in Intestinal Transplantation - Dugbartey , George J. (Current Innovations in Medicine and Medical Science Vol. 10, 2022)
The present study discusses recent advances in CO in intestinal transplantation, as well as the underlying molecular mechanisms of protection during the procurement, preservation, transplantation, and post-transplantation periods. A section of the chapter also discusses clinical translation of CO and its releasing molecules in the field of solid organ transplantation, as well as current translational challenges. Intestinal transplantation is a viable life-saving intervention reserved for patients with end-stage intestinal failure who are no longer able to receive total parenteral nutrition. This complex therapeutic procedure has received significant clinical attention over the last decade, demonstrating its evolution from an experimental beginning in the mid-20th century to a well-established clinical practise today. Despite several recent advances made in this field, there are several roadblocks that hamper the long-term success of intestinal transplantation. These include surgical manipulation during intestinal graft procurement, graft preservation and reperfusion damage resulting in poor graft quality, graft rejection, post-operative infectious complications, and ultimately negatively impacting long-term recipient survival. These challenges necessitate the search for new surgical techniques with potential to improve current intestinal transplantation protocol, reduce post-transplant complications and ensure long-term transplant recipient survival. Carbon monoxide (CO), a gas previously known for its toxicity and death at high concentrations, is rapidly evolving into a signalling molecule with biological usefulness and therapeutic potential at low physiological concentrations, which could overcome some of the challenges in current intestinal transplantation.